Current status and future perspectives of liquid biopsy in non-small cell lung cancer - Sunhee Chang; Jae Young Hur; Yoon-La Choi; Chang Hun Lee; Wan Seop Kim (Korean Society of Pathologists & the Korean Society for Cytopathology, 2020)
With advances in target therapy, molecular analysis of tumors is routinely required for treatment decisions in patients with advanced non-small cell lung cancer (NSCLC). Liquid biopsy refers to the sampling and analysis of circulating cell-free tumor DNA (ctDNA) in various body fluids, primarily blood. Because the technique is minimally invasive, liquid biopsies are the future in cancer management. Epidermal growth factor receptor (EGFR) ctDNA tests have been performed in routine clinical practice in advanced NSCLC patients to guide tyrosine kinase inhibitor treatment. In the near future, liquid biopsy will be a crucial prognostic, predictive, and diagnostic method in NSCLC. Here we present the current status and future perspectives of liquid biopsy in NSCLC.